A fragmentação do Direito Internacional no contexto do Direito do Mar: entre conflitos e mecanismos de coesão - Queiroz, Arthur Gustavo Saboya de (2019)
The phenomenon of the fragmentation of international law was formed during the twentieth century as a reflection of the expansion of the international legal sphere. Institutions and legal frameworks were set up to address a wide range of issues, without concern for coordination between them, as if international law were not in fact unified. What once appeared to be governed by general international law became a fragmented space between various specialties, with its own principles, rules and objectives. In this sense, problems have arisen around the clashes between these specialties. Despite directing international law to niches of action, elements of its unity remain: many issues do not turn only to one of these regimes, but congregate two themes or more. Thus, conflicts arise between incompatible standards, belonging to different "self-contained regimes", but that need to dialogue in practical cases. The law of the sea, in spite of being an apparent result of this process of fragmentation, also suffers from some of its consequences. There is, therefore, a detriment to the development of the subject, demanding the need to find ways to promote coherence between these rules. In this sense, the present dissertation proposed to analyze the effects of the fragmentation of International Law in the Law of the Sea. For this, it sought to answer a main question: in what way does the Fragmentation of International Law affect the consolidation of the Law of the Sea? With this question, it seeks to verify to what extent the Law of the Sea is affected by the phenomenon, if substantially or in a smaller form in relation to other areas of International Law. As a way of answering this question, it will draw on three more specific questions. Is international law unified or fragmented? This inquiry, in the initial part of the work, has the purpose of founding the theoretical bases of the research, delimiting the aforementioned fragmentary phenomenon. Next, it seeks to answer: what conflicts are found involving norms of Law of the Sea? In this point, it goes to the analysis of the Law of the Sea, involving not only the interaction between its norms, but also between its norms and those of other regimes involved by the International Law. Finally, is proposed to answer: how to solve these conflicts involving rules of Law of the Sea? Here, recognizing the existence of the aforementioned conflicts, we will seek to discuss and apply the possible ways of solving antinomies. For the accomplishment of this dissertation, a methodology based on a deductive method was chosen, reaching its conclusions from premises that it was sought to establish throughout its accomplishment. Moreover, considering that it seeks to identify, analyze and interpret facts, it presents itself as an explanatory research. It was developed, finally, from a wide bibliographical review, from the consult of articles, dissertations and books on the theory of law and general international law. It was also based on the study of documents, as it also drew on the analysis of legal texts such as treaties and case law, as well as information from bodies responsible for the development of international law, such as the United Nations International Law Commission.